Proteomic analysis of Down syndrome cerebrospinal fluid compared to late-onset and autosomal dominant Alzheimer´s disease - Laia Montoliu-Gaya; Shijia Bian; Eric B. Dammer; Daniel Alcolea; Mathias Sauer; Mitchell Martá-Ariza; Nicholas J. Ashton; Olivia Belbin; Johannes Fuchs; Caroline M. Watson; Lingyan Ping; Duc M. Duong; et al. (Nature Communications)
Abstract Almost all individuals with Down Syndrome (DS) develop Alzheimer’s disease (AD) by mid to late life. However, the degree to which AD in DS shares pathological changes with sporadic late-onset AD (LOAD) and autosomal dominant AD (ADAD) beyond core AD biomarkers such as amyloid-β (Aβ) and tau is unknown. Here, we used proteomics of cerebrospinal fluid from individuals with DS (n = 229) in the Down Alzheimer Barcelona Neuroimaging Initiative (DABNI) cohort to assess the evolution of AD pathophysiology from asymptomatic to dementia stages and compared the proteomic biomarker changes in DS to those observed in LOAD and ADAD. Although many proteomic alterations were shared across DS, LOAD, and ADAD, DS demonstrated more severe changes in immune-related proteins, extracellular matrix pathways, and plasma proteins likely related to blood-brain barrier dysfunction compared to LOAD. These changes were present in young adults with DS prior to the onset of Aβ or tau pathology, suggesting they are associated with trisomy 21 and may serve as risk factors for DSAD. DSAD showed an earlier increase in markers of axonal and white matter pathology and earlier changes in markers potentially associated with cerebral amyloid angiopathy compared to ADAD. The unique features of DSAD may have important implications for treatment strategies in this population.